Current Approaches of Salivary Glands Regeneration for Management of Xerostomia and Hyposalivation: A Narrative Review - Mahdani, Fatma Yasmin; Ayuningtyas, Nurina Febriyanti (Faculty of Dental Medicine Universitas Airlangga, 2023)
Background: The salivary glands are the organs that produce saliva and have a role keeping the oral cavity moist and lubricated. Salivary glands regeneration is important for developing treatments on management of xerostomia and hyposalivation because of the irreversible damage of salivary glands. Common causes include aging, polypharmacy, autoimmune disease, including Sjogren's syndrome, and head and neck radiation, in which xerostomia and hyposalivation having a substantial impact on patient health and wellbeing. Purpose: to describe current approach of salivary glands regeneration for management of xerostomia and hyposalivation through narrative review. Review(s): A literature search using Science Direct and PubMed yielded results between 1973 and 2022, and the results were evaluated to identify the most promising approaches and for future research. The keywords of the search strategy were